Carvedilol-Afforded Protection against Daunorubicin-Induced Cardiomyopathic Rats In Vivo: Effects on Cardiac Fibrosis and Hypertrophy. (14th April 2011) - Arozal, Wawaimuli; Sari, Flori R.; Watanabe, Kenichi; Arumugam, Somasundaram; Veeraveedu, Punniyakoti T.; Ma, Meilei; Thandavarayan, Rajarajan A.; Sukumaran, Vijayakumar; Lakshmanan, Arun Prasath; Kobayashi, Yoshiyasu; Mito, Sayaka; Soetikno, Vivian; et al.
Abstract : Anthracyclines, most powerful anticancer agents, suffer from their cardiotoxic effects, which may be due to the induction of oxidative stress. Carvedilol, a third-generation, nonselectiveβ -adrenoreceptor antagonist, possesses both reactive oxygen species (ROS) scavenging and ROS suppressive effects. It showed protective effects against daunorubicin- (DNR-) induced cardiac toxicity by reducing oxidative stress and apoptosis. This study therefore was designed to examine the effects of carvedilol on DNR-induced cardiomyopathic rats, focused on the changes of left ventricular function, cardiac fibrosis, and hypertrophy. Carvedilol increased survival rate, prevented systolic and diastolic dysfunction, and attenuated myocardial fibrosis and hypertrophy. DNR alone treated rats showed upregulated myocardial expression of ANP, PKC-α, OPN, and TGF-β 1 and downregulation of GATA-4 in comparison with control, and treatment with carvedilol significantly reversed these changes. The results of the present study add the available evidences on the cardioprotection by carvedilol when associated with anthracyclines and explain the mechanisms underlying the benefits of their coadministration.